The Determination of Kesongo Mud Volcano System Zone Using Seismic Interval Velocity at Potential Overpressure in The Tawun Formation, F Field, NE Java Basin - Burhannudinnur*, Muhammad; Koesmawardani, Wildan Tri (Aceh International Journal of Science and Technology, 2021)
The Mud Volcano System (SMV) is an interesting topic, especially the relatively shallow oil and gas basin in North East Java. The Tawun Formation is an alternating layer of claystone that is quite thick. It has been confirmed in several oil and gas fields as a potential layer of a mud volcano system, specifically the Kesongo Mud Volcano System. The existence of this system is a challenge to further exploration; therefore, zoning is essential. The data used in this research were interval velocity cubes which were re-picked in each of the two bin sizes (2x25m) as the primary data. The well and velocity data were performed to determine the deviation from the Normal Compaction Trend (NCT). Furthermore, the seismic interval was confirmed with drilling data such as mud log and mud weight. The value of preliminary pore pressure was also derived from interval velocity using Eaton Equation which is confirmed by mud weight data. The Zoning of the Mud Volcano System was carried out via a depth slice at 3D seismic intervals. The results showed that the Tawun Formation has a Mud Volcano System prone zone at a depth of 204 m and decreases in geometry as the depth increases. Meanwhile, the OP-1 zone was the safest zone for exploration, followed by OP-2 but requires passage through the Kesongo Mud Volcano System zone of 1000 m thickness.